REVIEW ON A NATIONAL MANGROVE MAPPING - Hartini, Sri; Saputro, Guridno Bintar; Suprajaka, Suprajaka; Niendyawati, Niendyawati (MAJALAH ILMIAH GLOBE, 2010)
Indonesia is the largest archipelagic country in the world with coastline span about 95,181 km. With such long coastline, coastal resources continuously support to the live of most Indonesian people. Mangroves are among the important coastal resources in terms of its economical and ecological functions. The mangroves have been severely deteriorated mostly due to the increasing exploitation as a result from the growing number of the population. Moreover, mangroves considered as a fragile ecosystem since it only grows in a unique area, which is in the tidal plain area. These problems have been discussed widely particularly to address how to preserve the functions of the mangroves. Planners and decision makers that concern on coastal resources and developments want to evaluate their changes overtime. Therefore, current data of the status of the mangroves nationally is highly demanded. This paper describes and evaluates the experience of the Center for Marine Resources Survey, Bakosurtanal in mapping mangroves Indonesia in 2009. Remote sensing approach had been used on the mangroves mapping. Remote sensing technique was considered as the most useful approach particularly due to the area that should be covered was very large. Besides that, mangroves can be easily recognized and delineated from most of satellite imageries. However, there are also some limitations on the application of remote sensing technology for mangroves mapping.Keywords: Mangrove, Remote Sensing, Mapping, IndonesiaÂ ABSTRAKIndonesia adalah Negara kepulauan terbesar di dunia, dengan panjang garis pantai mencapai lebih dari 95.181 km. Dengan garis pantai sepanjang itu, sumberdaya pesisir secara terus menerus menyokong kehidupan sebagian besar penduduk Indonesia. Mangrove merupakan salah satu sumberdaya pesisir yang penting baik dinilai secara ekonomi maupun secara ekologi. Sebagian dari mangrove tersebut mengalami kerusakan karena eksploitasi yang berlebihan seiring dengan pertambahan jumlah penduduk. Disamping itu, mangrove juga merupakan ekosistem yang rapuh karena mangrove hanya bisa tumbuh di lingkungan yang khusus, yaitu sepanjang area pasang surut saja. Permasalahan ini telah banyak dibahas, khususnya untuk mencari solusi guna melindunginya. Para perencana dan pengambil keputusan selalu ingin mengevaluasi perubahannya dari waktu ke waktu. Dengan demikian, data mengenai keberadaan mangrove terkini selalu diharapkan ketersediaannya. Tulisan ini memaparkan dan mengulas tentang pemetaan mangrove Indonesia yang dilakukan oleh Pusat Survei Sumber Daya Alam Laut, Bakosurtanal pada tahun 2009. Teknik penginderaan jauh telah digunakan sebagai pendekatan dalam pemetaan mangrove tersebut. Pendekatan ini dianggap sebagai alat yang sangat berguna karena mangrove dapat dengan mudah dikenali dan didelineasi dari citra satelit penginderaan jauh. Namun demikian, dalam aplikasi teknologi penginderaan jauh untuk pemetaan mangrove ini juga terdapat keterbatasan atau kekurangan.Kata kunci: Mangrove, Penginderaan Jauh, Pemetaan, Indonesia